Peran Organisasi Kepemudaan sebagai Wadah Generasi Muda: Organisasi Komisi Masyarakat Peduli Antikorupsi (KOMPAK) Lampung - Aftesia Labira Lauli; Mila Agustin; Yashinta Zahra Alfitri; Teki Prasetyo Sulaksono; Ana Mentari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This report presents the findings of an observation on the role of youth organizations as a platform for nurturing and developing the potential of the younger generation. The observation was conducted on several youth organizations in the local area that are actively involved in social, educational, and entrepreneurial activities. The results indicate that youth organizations contribute significantly to fostering leadership spirit, shaping positive character, and increasing youth participation in community development. However, challenges such as limited facility support and weak internal coordination remain obstacles. This report is expected to provide a realistic overview of the importance of strengthening youth organizations in the effort to develop a competitive and integrity-driven young generation.